A Cointegrated VAR Analysis of Stock Price Models: Fundamentals, Psychology and Structural Change. Issue 4 (1st October 2020) - Mangee, Nicholas; Goldberg, Michael D.
Abstract: This paper provides an empirical investigation of leading models of stock price fluctuations, including those based on canonical present value and behavioral considerations. It uses the cointegrated VAR framework to test the models' competing predictions concerning the roles of fundamentals, psychology, and structural change in driving fluctuations. We rely on a novel dataset from Bloomberg News to capture the influence of psychological factors and the broader information that market participants use contemplating stocks' fundamental values. We find that stock prices, earnings, and interest rates are cointegrated, but only when measures of psychological factors, a broader information set, and mean shifts are included in the cointegration relation. The results provide support for the scapegoat and imperfect knowledge models of stock prices, with weak evidence in favor of bubble models.